Antimicrobial effects of garlic (Allium sativum L.) - Strika, Ilma; Bašić, Aida; Halilović, Namir (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
Garlic has been used as a source of food and medicine for thousands of years. Given that the garlic contains different biologically active materials and acts as an antibiotic and a fungicide, the purpose of this research was to estimate the degree of sensitivity of three different Gram-positive bacteria: Staphylococcus aureus, methicillin-resistent Staphylococcus aures (MRSA) and Bacillus subtilis; two types of Gram-negative bacteria: Escherichia coli and Salmonella enteritidis; as well as the fungus Candida albicans. The degree of sensitivity of tested microbes with regards to the agency of fresh and thermally processed local and imported garlic was determined using the disc-diffusion method. Examined antimicrobial-test substances exhibited antibacterial effect on all tested gram-positive bacteria and gram-negative bacteria, as well as the fungistatic agency upon fungus C. albicans. The strongest antimicrobial effect on all tested species was exhibited by fresh local garlic. Preparates based on A. sativum could be introduced in clinical practice for the treatment of infections caused by C. albicans.